Industrial cutting of textile materials - Vilumsone-Nemes, Ineta (Woodhead Publishing, an imprint of Elsevier, 2018)
Annotation 'Industrial Cutting of Textile Materials' is a comprehensive guide to cutting room operations, offering step-by-step information on processes, technologies and best practice. This new edition is updated to present the latest advances in automated cutting technology, including advanced spreading methods and machines, advanced knife cutting systems, and pattern matching methods processing garment, home and technical textiles. Drawing on her extensive practical experience, the author begins by reviewing initial steps, such as unloading, sorting and quality control of materials, before discussing subsequent operations, including lay planning and marker making, manual and automated spreading and cutting, fusing of cut components, and final work operations such as sorting cut components for further joining.
Includes index.
Keywords: Textile industry.; Textile fabrics.; Cutting.; elektronické knihy; electronic books